2008
DOI: 10.1007/s10453-008-9100-8
|View full text |Cite
|
Sign up to set email alerts
|

Sources, impact and exchange of early-spring birch pollen in the Moscow region and Finland

Abstract: The paper presents an assessment of birch pollen seasons in Finland and Russia. The re-analysis covered the period from 1994 to 2005 and was focused on suspected long-range transport events that were recorded both in Moscow and at several Finnish sites. In order to trace the origin of airborne pollen before the onset of local pollination, we used both aerobiological and phenological observations combined with forward and adjoint (inverse) dispersion model simulations. It is shown that, although the Moscow regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 32 publications
3
66
0
Order By: Relevance
“…Sofiev et al, 2006a, b;Saarikoski et al, 2007;Siljamo et al, 2008;Sofiev et al, 2009;Saarnio et al, 2010; http://silam.fmi.fi). The model applications range from global to meso-beta scale (grid spacing down to 1 km).…”
Section: Silam (Finland Estonia Russia Lithuania and Spain)mentioning
confidence: 99%
See 1 more Smart Citation
“…Sofiev et al, 2006a, b;Saarikoski et al, 2007;Siljamo et al, 2008;Sofiev et al, 2009;Saarnio et al, 2010; http://silam.fmi.fi). The model applications range from global to meso-beta scale (grid spacing down to 1 km).…”
Section: Silam (Finland Estonia Russia Lithuania and Spain)mentioning
confidence: 99%
“…Saarikoski et al, 2007;Sofiev et al, 2009Sofiev et al, , 2011bSaarnio et al, 2010; and for selected biogenic aerosols, such as allergenic pollen (e.g. Sofiev et al, 2006bSofiev et al, , 2011Siljamo et al, 2008;Veriankaitë et al, 2010). The model is capable of four-dimensional variational data assimilation (Sofiev and Atlaskin, 2004).…”
Section: Silam (Finland Estonia Russia Lithuania and Spain)mentioning
confidence: 99%
“…Additionally, System for Integrated modeLling of Atmospheric coMposition (SILAM) simulations have been applied to trace the origin of LRT of airborne Betula pollen in Finland (Sofiev et al, 2006;Siljamo et al, 2008), Russia (Siljamo et al, 2008) and Lithuania (Veriankaite et al, 2010). Recently, the Monitoring of Atmospheric Composition and Climate (MACC, http://www.gmes-atmosphere.eu) regional multi-model sim ulations of Betula pollen dispersion in Europe (Sofiev et al, 2015) also showed that the models successfully reproduced the timing of the pollen season.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the 1990s, episodes of pollen dispersion on regional and continental scales have been addressed in numerous studies (Belmonte et al, 2000;Corden et al, 2002;Damialis and Gioulekas, 2005;Hjelmroos, 1992;Latalova et al, 2002;Mahura et al, 2007;Ranta and Satri, 2007;Ranta et al, 2011;Rantio-Lehtimaki, 1994;Siljamo et al, 2008c;Skjøth et al, 2008;Sofiev et al, 2012bSofiev et al, , 2006aYliPanula et al, 2009; see also reviews by Smith et al, 2014, andBergmann, 2013). It was shown that, although the features of each specific long-range transport episode vary widely, there may be a systematic pattern in the springtime pollen redistribution in Europe with prevailing transport directions, main source and receptor regions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…fmi.fi) by an international consortium within the scope of the POLLEN project of the Academy of Finland (Siljamo et al, 2012;Sofiev et al, 2012a). Various versions of the model have been used for forecasts of pollen distribution in Europe starting from 2005 (Sofiev et al, 2006a) and reanalysis of the flowering seasons back to 1997 (Siljamo et al, 2008c;Veriankaitė et al, 2010). The COSMO-ART birch module was developed at the University of Karlsruhe (Helbig et al, 2004;Vogel et al, 2008) and MeteoSwiss (Pauling et al, 2012;Zink et al, 2013) and is currently used for pollen forecasting for central and south-western Europe.…”
Section: Introductionmentioning
confidence: 99%